The educational ideal of the higher school and the idea of a university: the direction of transformations (Journal of Educational Sciences, 2016)
The problems of formation of education ideal, university ideas and their infl uence on the state are considered in the article. The Author pays attention on the state as social, economic organization for the process of socialization the whole society. The author proposes the solution ways on problems of development the concept of the educational ideal and its infl uence to countries and the social system as well as the university as one of the key parts of society.
Keywords: educational ideal; university; the idea of the university; the mission of the university; social organization; state; state administration of education.